Pemikiran Taqi Misbah Yazdi tentang Etika Islam Kontemporer - Nurasiah, Nurasiah (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
This article attempts to explain about the concept of Islamic ethics promulgated by Taqi Misbah Yazdi. Yazdi had placed himself as a proponent to the concept of rational ethics. To him, the propositions of ethics along with moral expressions have obviously explained a causality relation between an action and desired goals of ethics. Commands and prohibitions, in their prescriptive and descriptive forms, manifest the relation between actions and the objectives of ethics along with the legal consequences behind them. As a result, this matter deals with meaning, objective, the value of objectivity, and rationality. The extent of value and truth of certain action is determined by its objectives. Interestingly, this theory does not influence Yazdi to be trapped within utilitarianism materialist-positivist ethics nor it traps him into the dilemma of value relativity which occurs in the West?s theory of ethics. It can be obviously seen the originality and novelty of Yazdi?s thought; not in terms of the content of his theory, instead in his ability to use the ideas of the Western philosophy to clarify his opinions and concepts by combining Herbert Spencer?s evolutionism and Jeremy Bentham?s utilitarianism. Building his concepts on transcendental philosophy of Mulla Sadra, Yazdi?s moral causality has successfully preserve the transcendental logic and its esoteric dimensions; an achievement which could not even be attained by Muslim groups who reject the law of causality.